DESTINATION ATTRACTION POWER OF JATIBARANG AREA FROM TOURISM AND DESTINATION PERSPECTIVE - Budi - Prasetya; Karnowahadi - Karnowahadi; Suryadi - Poerbo; Subandi - Subandi (Politeknik Negeri Semarang, 2017)
ABSTRACTIndicator the atractions of tourism destinations with the highest score is an additional service that includes culinary, hospitality of the population, rural atmosphere, the comfort of the homestay (lodging), and the coolness of the air. The second rank of destination attractions are both a tour package that includes outbound, river tubing, visit on location of agricultural/livestock, rabbit train and gardening. While the third is a tourist attraction that includes the art of traditional culture, the natural landscape, the local event, water activities, as well as performances of the local music. Index analysis of the competitiveness of destinations generated some indicator value, i.e. the price competitiveness indicator (PCI), infrastructure development indicator (IDI), environmental indicator (EI), technology advancement indicator (TAI), human resources indicators (HRI), as well as social development indicators (SDI). But the results of the analysis showed that each indicator is still relatively low value and needs to be improved on an ongoing basis. Keywords: Tourism destination; Tourism attractions; Tourism competitiveness ABSTRAKIndikator atraktif dari destinasi wisata dengan nilai tertinggi adalah layanan tambahan yang meliputi kuliner, keramahan penduduk, suasana pedesaan, kenyamanan homestay (penginapan), dan kesejukan udara. Peringkat kedua dari objek wisata tujuan adalah paket wisata yang mencakup outbound, river tubing, kunjungan di lokasi pertanian / peternakan, kereta kelinci dan berkebun. Sedangkan yang ketiga adalah objek wisata yang meliputi seni budaya tradisional, pemandangan alam, aktivitas lokal, aktivitas air, serta pertunjukan musik lokal. Analisis indeks daya saing tujuan menghasilkan beberapa indikator nilai, yaitu indikator daya saing harga (PCI), indikator pembangunan infrastruktur (IDI), indikator lingkungan (AMDAL), indikator kemajuan teknologi (TAI), indikator sumber daya manusia (HRI), juga sebagai indikator pembangunan sosial (SDI). Namun hasil analisis menunjukkan bahwa setiap indikator masih tergolong rendah dan perlu ditingkatkan secara berkelanjutan. Kata kunci: Tujuan wisata; Daya tarik pariwisata; Daya saing pariwisata